2001
DOI: 10.1007/pl00021291
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and Intrajudge Reliability for Videofluoroscopic Swallowing Evaluation Measures

Abstract: Interjudge reliability for videofluoroscopic (VFS) swallowing evaluations has been investigated, and results have, for the most part, indicated that reliability is poor. While previous studies are well-designed investigations of interjudge reliability, few reports of intrajudge reliability are available for VFS measures derived from frame-by-frame analysis that clinicians typically employ. The purpose of this study was to examine the inter- and intrajudge reliability of VFS examination measures commonly used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
91
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(97 citation statements)
references
References 0 publications
5
91
0
1
Order By: Relevance
“…McCullough et al 35 examined common VF measures and found that statistics for interjudge reliability ranged from ϭ0 to 0.478; percentage agreement (calculated when was not possible) reached 92% on some variables. Intrajudge reliability has been greater in some studies but not in others.…”
Section: Videofluoroscopymentioning
confidence: 99%
“…McCullough et al 35 examined common VF measures and found that statistics for interjudge reliability ranged from ϭ0 to 0.478; percentage agreement (calculated when was not possible) reached 92% on some variables. Intrajudge reliability has been greater in some studies but not in others.…”
Section: Videofluoroscopymentioning
confidence: 99%
“…A reliable interpretation of images must be performed regardless of whether the images are from the same subject at different times or from a group of subjects at the same time for the VF to be regarded as a valid and reliable instrument of evaluation. VF studies show low levels of agreement for several parameters 16,25,29 . The parameter with the highest agreement regards the presence or absence of aspiration 10 , especially when compared with the assessment of severity of the vallecular residue 16,19,21,25 .…”
Section: Discussionmentioning
confidence: 93%
“…VF studies show low levels of agreement for several parameters 16,25,29 . The parameter with the highest agreement regards the presence or absence of aspiration 10 , especially when compared with the assessment of severity of the vallecular residue 16,19,21,25 . In the present study, the methodology used for assessing the percentage of vallecular residue was effective and demonstrated high/satisfactory reproducibility.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…A confiabilidade 42,43 e validade da ausculta cervical, quando comparadas aos estudos que utilizam a VDF 44,45,46 , variam muito entre os estudos. Contudo, cabe ressaltar que a VDF também apresenta baixa confiabilidade para julgamentos intra e inter juízes 47,48,49,50 . 8,17 .…”
Section: Discussionunclassified